Recovering from Morgellons and Neuro-cutaneous Syndrome (NCS): Patients’ Perspectives - Amin, Omar M. (Morgellon’s Disease and Neurocutaneous Syndrome (NCS): Cases and Recovery, 2021)
This presentation follows 15 NCS patients who have been using our Parasitology Center, Inc. (PCI) treatment protocol for healing from the Neurocutaneous Syndrome or Morgellons. By their own accounts, they recount their own experiences going through the steps and changes in symptoms and physical and psychological-emotional healing until they attained a state of recovery and balanced wellbeing; a dream come true.